Effects of dietary calcium and phosphorus deficiency and subsequent recovery on broiler chicken growth performance and bone characteristics. (4th December 2017) - Valable, A. S.; Narcy, A.; Duclos, M. J.; Pomar, C.; Page, G.; Nasir, Z.; Magnin, M.; Létourneau-Montminy, M. P.
Abstract : The ability of birds to modify dietary phosphorus utilisation when fed with low-phosphorus and calcium (Ca) diets was studied using different sequences of dietary phosphorus and Ca restriction (depletion) and recovery (repletion) during the grower and the finisher phases. A total of 3600 Ross 708 broilers were randomly divided into 10 replicate pens per treatment (60 per pen, six pens per block). Chicks were fed a common starter diet from days 0 to 10, then a grower control diet (C: 0.90% Ca, 0.39% non-phytate phosphorus, nPP), mid-level diet (M: 0.71% Ca, 0.35% nPP) or low Ca and nPP diet (L: 0.60% Ca, 0.30% nPP) from days 11 to 21, followed by a finisher diet C, M or L containing, respectively, 0.85%, 0.57% or 0.48% Ca and 0.35%, 0.29% or 0.24% nPP from days 22 to 37. Six treatment sequences were tested: CC, MM, LL, ML, LC and LM. Bone mineral content by dual-energy X-ray, tibia ash, toe ash weight and tibia breaking strength were measured on days 21 and 37. No significant effect was observed on growth performance throughout the experiment. Diet L reduced bone mineral content, breaking strength, tibia and toe ash by 9%, 13%, 11% and 10%, respectively, on day 21 (compared with diet C, for linear effect, P <0.05). On day 37, bone mineral content, breaking strength, tibia and toe ash remained lower compared with control values (CC v . MM v . LL, P <0.05 for linear and quadratic effects). Mineral depletion duration (ML v . LL) did not affect bone mineral status. Replenishing with the C diet during the finisher phase (LC) restored bone mineral content, tibia ash and toe ash weight better than the M diet did, but not to control levels (CC v . LC v . LM, for linear effect, P <0.05). These results confirm that dietary Ca and nPP may be reduced in the grower phase without affecting final growth performance or breaking strength as long as the finisher diet contains sufficient Ca and nPP. The practical applications of this strategy require further study in order to optimise the depletion and repletion steps.